2020
DOI: 10.1111/cge.13705
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic regulation of abdominal aortic aneurysms

Abstract: Abdominal aortic aneurysms (AAAs) are focal dilations of the aorta that develop from degenerative changes in the media and adventitia of the vessel. Ruptured AAAs have a mortality of up to 85%, thus it is important to identify patients with AAA at increased risk for rupture who would benefit from increased surveillance and/or surgical repair.Although the exact genetic and epigenetic mechanisms regulating AAA formation are not completely understood, Mendelian cases of AAA, which result from pathologic var-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 137 publications
0
30
0
Order By: Relevance
“…MiRNAs are short (~20 base pair long), single-stranded non-coding RNA that directly regulate gene expression and exert a wide range of cellular functions [ 78 ]. They negatively regulate gene expression by degrading mRNA or mimicking small interfering RNA (siRNA) and inhibiting translation.…”
Section: Vsmc-mediated Extracellular Matrix Production and Degradamentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are short (~20 base pair long), single-stranded non-coding RNA that directly regulate gene expression and exert a wide range of cellular functions [ 78 ]. They negatively regulate gene expression by degrading mRNA or mimicking small interfering RNA (siRNA) and inhibiting translation.…”
Section: Vsmc-mediated Extracellular Matrix Production and Degradamentioning
confidence: 99%
“…miRNAs are initially transcribed as pi-miRNAs, longer primary transcripts, that are processed by the ribonuclease enzyme complex Drosha/DGCR8, followed by Dicer, and incorporation into the RNA-induced silencing complex (RISC) [ 79 ]. Mature miRNA is able to pair with a highly conserved seed sequence within the 3’ untranslated region (UTR) of potentially multiple target genes [ 78 ]. A wide variety of miRNAs have been studied in AAA that target specific genes to regulate VSMC plasticity as well as ECM degradation and inflammation ( Table 2 ).…”
Section: Vsmc-mediated Extracellular Matrix Production and Degradamentioning
confidence: 99%
“…An abdominal aortic aneurysm (AAA) is a pathological enlargement of the infrarenal aorta that can potentially be life‐threatening if progressing to rupture 1,2 . An important aspect of AAA formation and progression, apart from host genetic background and lifestyle factors (e.g., diet, smoking), are environmental factors, which are crucial in the regulation of inflammatory processes 3–5 . Several studies have suggested that bacterial and viral pathogens, as well as host response, may be involved in the formation of AAA and/or accelerate its progression 6–22 .…”
Section: Introductionmentioning
confidence: 99%
“…AAA has been attributed to many environmental and genetic factors. 7 Genetic studies have identified many novel loci for AAA. [8][9][10][11] Although the pathogenesis of AAA is unclear, accumulating evidence supports a central role for inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…AAA has been attributed to many environmental and genetic factors. 7 Genetic studies have identified many novel loci for AAA. 8–11 …”
Section: Introductionmentioning
confidence: 99%